Design Criteria of Modern Shopping Centre Building Based on Public Pedestrian Space - Kapindro Hari Sasmita; Bambang Soemardiono; Vincentius Totok Noerwasito (Journal of Architecture & Environment, 2020)
Mobility contributes to the quality of life (Muller, 2016). In Indonesia, shopping centers and pedestrian spaces have not been supporting each other to accommodate public pedestrians. It lets people drive more automobiles instead of walking even though their settlements are convenient to the commercial places. This problem is further causing other matters such as traffic congestion, accidence, air-pollution, anxiety, and so on. By considering the problem, it is important to transform the design criteria of the modern shopping centers to be not only serving as a commercial destination but also space to provide mobility for public pedestrians in an urban environment. This research is aimed to identify the design criteria of modern shopping centers based on public pedestrian space. The criteria are expected to be a new standard for planning and designing future shopping centers in Indonesian cities. The Evaluative Method is utilized in this research involving a theory of Urban Mobility as the main parameter and three precedents as the objects. The similarities between the precedents could be considered as important design criteria that need to be formulated by utilizing aspects of the theory. As a result, the shopping centers should be designed as a complex of building masses to allow mobility for public pedestrians which need support by transit system and facility. Any integrated circulation with another building with different use also promotes pedestrian activity. The character of the building form or façade should be able to balance the rigid character of the surrounding urban area.